Borrowing constraints and savings in Turkey - Sumru Altuğ; Melih Can Fırat (Koç University-TÜSİAD Economic Research Forum (ERF), 2018)
The Turkish macroeconomic experience since 2002 has been characterized by three striking trends: (1) an accelerated growth rate of income, (2) a sharp decline in the real interest rate, and (3) a sustained fall in the saving rate of different age-groups. During the same period, there has also been a significant increase in access to credit by Turkish households. In this paper, we argue that a model which incorporates a borrowing constraint mechanism together with the observed increases in the expected growth rate of income and the substantial declines in the real interest rate is able to explain the change in saving across cohorts in Turkey over the last decade. We provide both micro-level evidence on the age-saving profile for Turkey as well as quantitative results from a simple three-period OLG framework with borrowing constraints to account for the change in the saving rate for different age-groups between 2004 and 2014.
Keywords: C78; D61; D78; I20; 330; Borrowing constraints; life-cycle household saving; nonlinear estimation; Turkey